Administration or management of European Union funds? - Guz, Hubert (Journal of Public Governance, 2013)
The paper presents methods of European Union cohesion policy management in comparison to the models of public administration. History of the union cohesion policy indicates, that in past programming periods, this policy has drawn from the various paradigms of public administration in a different scale and scope.There is a short analysis of the four models of public administration: old public administration, public administration, new public management and public governance with designation of their main features. These features are related to the mechanisms of cohesion policy management.Systems and tools of cohesion policy management in Poland, on a regional level, in programming period 2004-2006, mainly based on classic public administration model. In programming period 2007-2013, the idea of new public management and elements of public governance became more and more popular. Solutions planned for the coming financial perspective 2014-2020 are shown, especially a wider use of public governance mechanisms on regional level, according to the European, horizontal principle of partnership.In the article are presented arguments confirming the thesis about slow evolution of cohesion policy management in Polish regions from administration to management, even to governance.